A Spectrum of Neural Autoantigens, Newly Identified by Histo-Immunoprecipitation, Mass Spectrometry, and Recombinant Cell-Based Indirect Immunofluorescence - Scharf, Madeleine; Miske, Ramona; Kade, Stephanie; Hahn, Stefanie; Denno, Yvonne; Begemann, Nora; Rochow, Nadine; Radzimski, Christiane; Brakopp, Stephanie; Probst, Christian; Teegen, Bianca; Stöcker, Winfried; et al. (Frontiers in Immunology, 2018)
Background: A plurality of neurological syndromes is associated with autoantibodies against neural antigens relevant for diagnosis and therapy. Identification of these antigens is crucial to understand the pathogenesis and to develop specific immunoassays. Using an indirect immunofluorescence assay (IFA)-based approach and applying different immunoprecipitation (IP), chromatographic and mass spectrometric (MS) protocols it was possible to isolate and identify a spectrum of autoantigens from brain tissue. Methods: Sera and CSF of 320 patients suspected of suffering from an autoimmune neurological syndrome were comprehensively investigated for the presence of anti-neural IgG autoantibodies by IFA using mosaics of biochips with brain tissue cryosections and established cell based recombinant antigen substrates as well as immunoblots. Samples containing unknown brain tissue-specific autoantibodies were subjected to IP with cryosections of cerebellum and hippocampus (rat, pig, monkey) immobilized to glass slides or with lysates produced from homogenized tissue, followed by SDS-PAGE, tryptic digestion, and MALDI-TOF MS analysis. Identifications were confirmed by IFA with recombinant HEK293 cells and by neutralizing the patients’ autoantibodies with the respective recombinantly expressed antigens in the tissue based immunofluorescence test. Results: Most samples used in this study produced speckled, granular or homogenous stainings of the hippocampal and cerebellar molecular and/or granular layers. Others exclusively stained the Purkinje cells. Up to now, more than 20 different autoantigens could be identified by this approach, among them ATP1A3, CPT1C, Flotillin1/2, ITPR1, NBCe1, NCDN, RGS8, ROCK2 and Syntaxin1b as novel autoantigens. Discussion: The presented antigen identification strategy offers an opportunity for identifying up to now unknown neural autoantigens. Recombinant cell substrates containing the newly identified antigens can be used in serology and the clinical relevance of the autoantibodies can be rapidly evaluated in cohort studies.